Signaling domains of cancer-associated glycolipids - Koichi Furukawa; Yuhsuke Ohmi; Kazunori Hamamura; Yuji Kondo; Yuki Ohkawa; Kei Kaneko; Noboru Hashimoto; Farhana Yesmin; Robiul H. Bhuiyan; Orie Tajima; Keiko Furukawa (Glycoconjugate Journal, 2022)

A molecular assessment of species diversity in Tympanopleura and Ageneiosus catfishes (Auchenipteridae: Siluriformes) - Shizuka Hashimoto; Lúcia H. Rapp Py‐Daniel; Jacqueline S. Batista (Journal of Fish Biology, 2020)
In order to test the congruence of genetic data to the morphologically defined Neotropical catfish genera Tympanopleura and Ageneiosus and explore species diversity, we generated 17 DNA barcodes from five of six species of Tympanopleura and 12 of 13 species of Ageneiosus . To discriminate limits between species, an automatic barcode gap discovery (ABGD), a generalised mixed yule‐coalescent model (GYMC) and fixed distance thresholds Kimura two‐parameter (K2P; 3%) were used to discriminate putative species limits from the DNA barcodes. The ABGD, GMYC and K2P methods agreed by each generating 13 clusters: six in Tympanopleura (five nominal plus one undescribed species) and seven in Ageneiosus . These clusters corresponded broadly to the described species, except in the case of the Ageneiosus ucayalensis group ( A. akamai , A. dentatus , A. intrusus , A. ucayalensis , A. uranophthalmus and A. vittatus ). Haplotype sharing and low divergences may have prevented molecular methods from distinguishing these species. We hypothesise that this is the result of a recent radiation of a sympatric species group distributed throughout the Amazon Basin. One putative new species of Tympanopleura was also supported by the molecular data. These results taken together highlight the utility of molecular methods such as DNA barcoding in understanding patterns of diversification across large geographic areas and in recognising overlooked diversity.

Metabolome Analysis Reveals Dermal Histamine Accumulation in Murine Dermatitis Provoked by Genetic Deletion of P-Glycoprotein and Breast Cancer Resistance Protein - Naoto Hashimoto; Noritaka Nakamichi; Hikari Nanmo; Kei-ichi Kimura; Yusuke Masuo; Yasuyuki Sakai; Alfred H. Schinkel; Shinichi Sato; Tomoyoshi Soga; Yukio Kato (Pharmaceutical Research, 2019)

Altered Notch Signaling in Developing Molar Teeth of Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP)-Deficient Mice - B. D. Fulop; B. Sandor; E. Szentleleky; E. Karanyicz; D. Reglodi; B. Gaszner; R. Zakany; H. Hashimoto; T. Juhasz; A. Tamas (Journal of Molecular Neuroscience, 2019)

Mitochondrial orf463 causing male sterility in radish is possessed by cultivars belonging to the ‘Niger’ group - H. Yamagishi; Y. Tanaka; S. Shiiba; A. Hashimoto; A. Fukunaga; T. Terachi (Euphytica, 2019)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

In situ electrochemical enrichment and isolation of a magnetite‐reducing bacterium from a high pH serpentinizing spring - Annette R. Rowe; Miho Yoshimura; Doug E. LaRowe; Lina J. Bird; Jan P. Amend; Kazuhito Hashimoto; Kenneth H. Nealson; Akihiro Okamoto (Environmental Microbiology, 2017)
Summary Serpentinization is a geologic process that produces highly reduced, hydrogen‐rich fluids that support microbial communities under high pH conditions. We investigated the activity of microbes capable of extracellular electron transfer in a terrestrial serpentinizing system known as ‘The Cedars’. Measuring current generation with an on‐site two‐electrode system, we observed daily oscillations in current with the current maxima and minima occurring during daylight hours. Distinct members of the microbial community were enriched. Current generation in lab‐scale electrochemical reactors did not oscillate, but was correlated with carbohydrate amendment in Cedars‐specific minimal media. Gammaproteobacteria and Firmicutes were consistently enriched from lab electrochemical systems on δ‐MnO 2 and amorphous Fe(OH) 3 at pH 11. However, isolation of an electrogenic strain proved difficult as transfer cultures failed to grow after multiple rounds of media transfer. Lowering the bulk pH in the media allowed us to isolate a Firmicutes strain ( Paenibacillus sp .). This strain was capable of electrode and mineral reduction (including magnetite) at pH 9. This report provides evidence of the in situ activity of microbes using extracellular substrates as sinks for electrons at The Cedars, but also highlights the potential importance of community dynamics for supporting microbial life through either carbon fixation, and/or moderating pH stress.

Structural and Morphometric Comparison of Lower Incisors in PACAP-Deficient and Wild-Type Mice - B. Sandor; K. Fintor; D. Reglodi; D. B. Fulop; Z. Helyes; I. Szanto; P. Nagy; H. Hashimoto; A. Tamas (Journal of Molecular Neuroscience, 2016)

Relationships between capture-site characteristics and capture levels of the invasive mongoose on Amami-Oshima Island, Japan - H. Komine; K. Takeshita; S. Abe; T. Ishikawa; M. Kimura; T. Hashimoto; K. Kitaura; T. Morosawa; K. Seki; K. Kaji (Biological Invasions, 2016)

Impact of bacterial coinfection on clinical outcomes in pneumococcal pneumonia - S. Kumagai; T. Ishida; H. Tachibana; Y. Ito; A. Ito; T. Hashimoto (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Magnetically-modified natural biogenic iron oxides for organic xenobiotics removal - I. Safarik; J. Filip; K. Horska; M. Nowakova; J. Tucek; M. Safarikova; H. Hashimoto; J. Takada; R. Zboril (International Journal of Environmental Science and Technology, 2015)

Structural and Morphometric Comparison of the Molar Teeth in Pre-eruptive Developmental Stage of PACAP-Deficient and Wild-Type Mice - B. Sandor; K. Fintor; Sz. Felszeghy; T. Juhasz; D. Reglodi; L. Mark; P. Kiss; A. Jungling; B. D. Fulop; A. D. Nagy; H. Hashimoto; R. Zakany; et al. (Journal of Molecular Neuroscience, 2014)

Comparative Protein Composition of the Brains of PACAP-Deficient Mice Using Mass Spectrometry-Based Proteomic Analysis - G. Maasz; Z. Pirger; D. Reglodi; D. Petrovics; J. Schmidt; P. Kiss; A. Rivnyak; H. Hashimoto; P. Avar; E. Jambor; A. Tamas; B. Gaszner; et al. (Journal of Molecular Neuroscience, 2014)

Examination of Calcium-Binding Protein Expression in the Inner Ear of Wild-Type, Heterozygous and Homozygous Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP)-Knockout Mice in Kanamycin-Induced Ototoxicity - A. Nemeth; K. Szabadfi; B. Fulop; D. Reglodi; P. Kiss; J. Farkas; B. Szalontai; R. Gabriel; H. Hashimoto; A. Tamas (Neurotoxicity Research, 2014)

Effects of Pituitary Adenylate Cyclase Activating Polypeptide on Human Sperm Motility - R. Brubel; P. Kiss; A. Vincze; A. Varga; A. Varnagy; J. Bodis; L. Mark; E. Jambor; G. Maasz; H. Hashimoto; Zs. Helyes; G. Toth; et al. (Journal of Molecular Neuroscience, 2012)

PACAP is an Endogenous Protective Factor—Insights from PACAP-Deficient Mice - D. Reglodi; P. Kiss; K. Szabadfi; T. Atlasz; R. Gabriel; G. Horvath; P. Szakaly; B. Sandor; A. Lubics; E. Laszlo; J. Farkas; A. Matkovits; et al. (Journal of Molecular Neuroscience, 2012)

Characteristics and osteogenic differentiation of stem/progenitor cells in the human dental follicle analyzed by gene expression profiling - H. Aonuma; N. Ogura; K. Takahashi; Y. Fujimoto; S. Iwai; H. Hashimoto; K. Ito; Y. Kamino; T. Kondoh (Cell and Tissue Research, 2012)

‘Better off alone than in bad company’: agonistic colour display in mimetic juveniles of two ephippid species - B. Barros; Y. Sakai; H. Hashimoto; K. Gushima; M. Vallinoto (Journal of Fish Biology, 2012)
Comparative field observations of agonistic interactions in juvenile leaf‐mimicking Platax orbicularis and Chaetodipterus faber (Ephippidae) were conducted in coastal waters of the Pacific and Atlantic Oceans. Similar agonistic behaviour was observed in the two species, in which individuals stopped displaying their mimetic colouration during encounters with conspecifics, to display conspicuous colours, such as transverse stripes along the body. These events were observed occasionally, almost invariably in individuals of smaller body size. Larger‐bodied individuals of both species spent less time in agonistic displays. The absolute size of the fish, however, did not appear to affect the outcome of the encounter, suggesting that dominance is a temporary condition, based on the relative size of the opponents during encounters.

Development and characterization of microsatellite loci in Phractocephalus hemioliopterus (Siluriformes: Pimelodidae) and their cross-species amplification in six related species - C. A. Souza; D. T. Hashimoto; L. H. G. Pereira; C. Oliveira; F. Foresti; F. Porto-Foresti (Conservation Genetics Resources, 2012)

Identification and characterization of polymorphic microsatellite loci in the blue shark Prionace glauca , and cross‐amplification in other shark species - F. F. Mendonça; L. H. F. Ussami; D. T. Hashimoto; L. H. G. Pereira; F. Porto‐Foresti; C. Oliveira; O. B. F. Gadig; F. Foresti (Journal of Fish Biology, 2012)
Two to 14 alleles were found to be segregating per locus (mean 5·2), with observed and expected heterozygosities ranging from 0·08 to 0·78 and 0·08 to 0·94, respectively. Cross‐amplification of six of these microsatellite loci indicated that they are also polymorphic in three species of Carcharhiniformes and two species of Lamniformes. The newly developed primers reported here constitute a useful tool for genetic population analyses on Prionace glauca and, potentially, other related species.

Comparative Examination of Inner Ear in Wild Type and Pituitary Adenylate Cyclase Activating Polypeptide (PACAP)-Deficient Mice - A. Tamas; K. Szabadfi; A. Nemeth; B. Fulop; P. Kiss; T. Atlasz; R. Gabriel; H. Hashimoto; A. Baba; N. Shintani; Zs. Helyes; D. Reglodi (Neurotoxicity Research, 2012)

Effects of renal function on the pharmacokinetics and pharmacodynamics of prophylactic cefazolin in cardiothoracic surgery - T. Kosaka; K. Hosokawa; N. Shime; F. Taniguchi; T. Kokufu; S. Hashimoto; H. Fujiwara; H. Yaku; N. Sugioka; K. Okada; N. Fujita (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Mice Deficient in Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) are More Susceptible to Retinal Ischemic Injury In Vivo - K. Szabadfi; T. Atlasz; P. Kiss; B. Danyadi; A. Tamas; Zs. Helyes; H. Hashimoto; N. Shintani; A. Baba; G. Toth; R. Gabriel; D. Reglodi (Neurotoxicity Research, 2012)

Removal of Cr(VI) from aqueous solutions by the culm of bamboo grass treated with concentrated sulfuric acid - M. Koroki; S. Saito; H. Hashimoto; T. Yamada; Masakazu Aoyama (Environmental Chemistry Letters, 2010)

Antifouling properties of tough gels against barnacles in a long-term marine environment experiment - T. Murosaki; T. Noguchi; K. Hashimoto; A. Kakugo; T. Kurokawa; J. Saito; Y. M. Chen; H. Furukawa; J. P. Gong (Biofouling, 2009)

Complete nucleotide sequence of asparagus virus 3 - M. Hashimoto; J. Ozeki; K. Komatsu; H. Senshu; S. Kagiwada; T. Mori; Y. Yamaji; S. Namba (Archives of Virology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Clathrin is involved in organization of mitotic spindle and phragmoplast as well as in endocytosis in tobacco cell cultures - H. Tahara; E. Yokota; H. Igarashi; H. Orii; M. Yao; S. Sonobe; T. Hashimoto; P. J. Hussey; T. Shimmen (Protoplasma, 2007)

Hypoxia-induced hyaluronan synthesis by articular chondrocytes: the role of nitric oxide - K. Hashimoto; K. Fukuda; K. Yamazaki; N. Yamamoto; T. Matsushita; S. Hayakawa; H. Munakata; C. Hamanishi (Inflammation Research, 2006)

Involvement of Aquaporin-5 Water Channel in Osmoregulation in Parotid Secretory Granules - M. Matsuki; S. Hashimoto; M. Shimono; M. Murakami; J. Fujita-Yoshigaki; S. Furuyama; H. Sugiya (The Journal of Membrane Biology, 2005)

Horizontal and Vertical Distribution of Estrogenic Activities in Sediments and Waters from Tokyo Bay, Japan - S. Hashimoto; A. Horiuchi; T. Yoshimoto; M. Nakao; H. Omura; Y. Kato; H. Tanaka; K. Kannan; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 2005)

Current Levels of Dioxins in Surface Soils from Santiago, Chile - Y. Takazawa; R. Verdugo; P. Richter; K. Kitamura; J.-W. Choi; S. Hashimoto; H. Ito; Y. Shibata; M. Morita (Bulletin of Environmental Contamination and Toxicology, 2004)

High frequency Agrobacterium-mediated transformation and plant regeneration via direct shoot formation from leaf explants in Beta vulgaris and Beta maritima - H. Hisano; Y. Kimoto; H. Hayakawa; J. Takeichi; T. Domae; R. Hashimoto; J. Abe; S. Asano; A. Kanazawa; Y. Shimamoto (Plant Cell Reports, 2004)

Centripetal bias on preparation for smooth pursuit eye movements based on the anticipation - H. Tabata; K. Hashimoto; N. Inaba; K. Kawano (Experimental Brain Research, 2004)

Phylogenetic relationships of deep-sea mussels of the genus Bathymodiolus (Bivalvia: Mytilidae) - J.-I. Miyazaki; M. Shintaku; A. Kyuno; Y. Fujiwara; J. Hashimoto; H. Iwasaki (Marine Biology, 2004)

Sleeping mound construction using coral fragments by the rockmover wrasse - S. Takayanagi; Y. Sakai; H. Hashimoto; K. Gushima (Journal of Fish Biology, 2003)
The rockmover wrasse Novaculichthys taeniourus was observed using coral fragments for mound construction on the reefs of Kuchierabu‐jima Island, Japan. The wrasse heaped between four and 71 pieces of coral fragments on each sand mound, and dived into the mound just before sunset. Coral fragments may facilitate the retention of sleeping sites under competition with other sand‐diving wrasses.

Differentiation in the status of self-incompatibility among Calibrachoa species (Solanaceae) - T. Tsukamoto; T. Ando; H. Watanabe; H. Kokubun; G. Hashimoto; U. Sakazaki; E. Surez; E. Marchesi; K. Oyama; T. Kao (Journal of Plant Research, 2002)

Differential effects of bacterial toxins on mitogenic actions of sodium fluoride and those of aluminum fluoride in human TE85 osteosarcoma cells - Hideki Hashimoto; K.-H. William Lau (Molecular and Cellular Biochemistry, 2001)

Construction of a high-resolution linkage map of a rice brown planthopper (Nilaparvata lugens Stål) resistance gene bph2 - H. Murai; Z. Hashimoto; P. N. Sharma; T. Shimizu; K. Murata; S. Takumi; N. Mori; S. Kawasaki; C. Nakamura (Theoretical and Applied Genetics, 2001)

A method for detecting myocardial abnormality by using a total current-vector calculated from ST-segment deviation of a magnetocardiogram signal - A. Kandori; H. Kanzaki; K. Miyatake; S. Hashimoto; S. Itoh; N. Tanaka; T. Miyashita; K. Tsukada (Medical & Biological Engineering & Computing, 2001)

A method for detecting myocardial abnormality by using a current-ratio map calculated from an exercise-induced magnetocardiogram - A. Kandori; H. Kanzaki; K. Miyatake; S. Hashimoto; S. Itoh; N. Tanaka; T. Miyashita; K. Tsukada (Medical & Biological Engineering & Computing, 2001)

Structure of the infected cell protein 0 gene of canine herpesvirus - M. Miyoshi; M. Takiguchi; J. Yasuda; A. Hashimoto; A. Takada; K. Okazaki; H. Kida (Archives of Virology, 2000)

Antibacterial characteristics of magnesium oxide powder - J. Sawai; H. Kojima; H. Igarashi; A. Hashimoto; S. Shoji; T. Sawaki; A. Hakoda; E. Kawada; T. Kokugan; M. Shimizu (World Journal of Microbiology and Biotechnology, 2000)

Genetic contribution of the BAT2 gene microsatellite polymorphism to the age-at-onset of insulin-dependent diabetes mellitus - M. Hashimoto; N. Nakamura; H. Obayashi; F. Kimura; A. Moriwaki; G. Hasegawa; H. Shigeta; Y. Kitagawa; K. Nakano; M. Kondo; M. Ohta; M. Nishimura (Human Genetics, 1999)

Genetic contribution of the BAT2 gene microsatellite polymorphism to the age-at-onset of insulin-dependent diabetes mellitus - M. Hashimoto; N. Nakamura; H. Obayashi; F. Kimura; A. Moriwaki; G. Hasegawa; H. Shigeta; Y. Kitagawa; K. Nakano; M. Kondo; M. Ohta; M. Nishimura (Human Genetics, 1999)

A Comparison of the Plasma Fructose Concentrations in Dogs and Cats and Changes in the Fructose Concentrations in Dogs Following Intravenous Administration of Fructose - T. Arai; K. Hashimoto; H. Muzutani; T. Kawabata; T. Sako; T. Washizu (Veterinary Research Communications, 1999)

Glycogen storage disease III subtypes and muscle weakness during childhood - M. Okubo; A. Horinishi; M. Hashimoto; H. Kanno; T. Murase (Human Genetics, 1999)

Structure of the immediate early gene of canine herpesvirus - M. Miyoshi; M. Takiguchi; J. Yasuda; A. Hashimoto; A. Takada; K. Okazaki; H. Kida (Archives of Virology, 1999)

Interaction of citrus juices with pranidipine, a new 1,4-dihydropyridine calcium antagonist, in healthy subjects - K. Hashimoto; T. Shirafuji; H. Sekino; O. Matsuoka; H. Sekino; O. Onnagawa; T. Okamoto; S. Kudo; J. Azuma (European Journal of Clinical Pharmacology, 1998)

Enhanced human tumor cell transplantability in a new congenic immunodeficient mouse; KSN-BNX - Y. Ishigaki; K. Yasuda; N. Hashimoto; H. Nikaido; O. Nikaido; J. -I. Hayakawa (Folia Microbiologica, 1998)

Urine-associated horizontal transmission of Seoul virus among rats - H. Kariwa; M. Fujiki; K. Yoshimatsu; J. Arikawa; I. Takashima; N. Hashimoto (Archives of Virology, 1998)

Urine-associated horizontal transmission of Seoul virus among rats - H. Kariwa; M. Fujiki; K. Yoshimatsu; J. Arikawa; I. Takashima; N. Hashimoto (Archives of Virology, 1998)

Effects of carp serum on the growth of goldfish fin cells in early passage - H. Hashimoto; H. Toyohara; Y. Yokoyama; M. Sakaguchi; K. Ozato; Y. Wakamatsu (Journal of Fish Biology, 1997)
The culture medium supplemented with carp serum and fetal bovine serum (FBS) promoted cell growth significantly and induced morphological change of goldfish fin cells in early passage as compared to the medium containing FBS alone. However, these effects were not observed in RBCF‐1, a cell line established from the goldfish fin. The sensitivity of the cells in early passage to carp serum suggests the following possibilities: (1) cells in early passage retain the ability to respond to growth‐promoting factors specifically included in carp serum; and (2) this ability is lost during the process of long‐term culture and/or long‐term culture in FBS eliminates cell groups showing high dependency of cell growth on carp serum.

Modes of Seoul virus infections: persistency in newborn rats and transiency in adult rats - H. Kariwa; M. Kimura; S. Yoshizumi; J. Arikawa; K. Yoshimatsu; I. Takashima; N. Hashimoto (Archives of Virology, 1996)

Lactoferrin-mediated protection of the host from murine cytomegalovirus infection by a T-cell-dependent augmentation of natural killer cell activity - K. Shimizu; H. Matsuzawa; K. Okada; S. Tazume; S. Dosako; Y. Kawasaki; K. Hashimoto; Y. Koga (Archives of Virology, 1996)

Analysis of target organs for the latency of murine cytomegalovirus DNA using specific pathogen free and germfree mice - H. Matsuzawa; K. Shimizu; K. Okada; K. Ando; K. Hashimoto; Y. Koga (Archives of Virology, 1995)

Molecular cloning and sequence determination of the peplomer protein gene of feline infectious peritonitis virus type I - K. Motokawa; T. Hohdatsu; C. Aizawa; H. Koyama; H. Hashimoto (Archives of Virology, 1995)

Antibody-dependent enhancement of hantavirus infection in macrophage cell lines - J. -S. Yao; H. Kariwa; I. Takashima; K. Yoshimatsu; J. Arikawa; N. Hashimoto (Archives of Virology, 1992)

Preparation of Japanese encephalitis virus nonstructural protein NS1 obtained from culture fluid of JEV-infected Vero cells - T. Lee; K. Watanabe; C. Aizawa; A. Nomoto; H. Hashimoto (Archives of Virology, 1991)

Enhanced production of interferon by ultraviolet irradiation and pretreatment with interferon in human diploid cells stimulated with polyinosinate-polycytidilate - H. Komatsu; N. Maehara; K. Shimoda; H. Hashimoto; T. Mori; T. Lee; S. Makino; M. Matumoto (Archives of Virology, 1982)

Neurovirulence in cynomolgus monkeys of enterovirus 71 isolated from a patient with hand, foot and mouth disease - I. Hashimoto; A. Hagiwara; H. Kodama (Archives of Virology, 1978)

Quantitative description of end plate current and its reconstruction - H. Yagi; T. Hashimoto; K. Sugimoto (Biological Cybernetics, 1977)